Nilai-Nilai Pendidikan Islam dalam Meningkatkan Persaudaraan Menurut Al-Qur’an Surat Al-Hujurat Ayat 10 - Nur Atiatul 'Ilma; Muchotob Hamzah; Muhtar Sofwan Hidayat (DAS Institute, 2024)
The problem taken in this paper is how to increase brotherhood through the application of Islamic educational values according to the Koran, Al-Hujurat verse 10 and how to implement it to increase brotherhood. This paper uses library research methods. The results of this paper suggest that in an effort to increase brotherhood, namely caring, respecting each other, helping each other, being humble and not arrogant so that discrimination does not occur both at school and outside school. The values of Islamic education can be instilled in students through habits such as congregational prayer, mutual cooperation, and building relationships.